TI_GERICHTE 12.2005.45 vom 9. Februar 2006 , banca - prelevamenti dal conto del cliente - ordine telefonico confermato via fax - TI Tribunale d'appello (2006)
banca - prelevamenti dal conto del cliente - ordine telefonico confermato via fax